Zafry Zamzam, Pandangan Kebangsaan Antara Unitarisme Atau Federalisme Untuk Tatanan Kenegaraan Republik Indonesia - Fazakkir Zamzam; Siti Frosidha Hez; Faizatunniza Faizatunniza; Fakhry Zamzam (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
This research is aimed at reexamining the big ideas of the national warrior from Kalimantan, Zafry Zamzam, who has always been persistent in choosing Unitarism as the state administration of the Republic of Indonesia which he initiated since the Dutch and Japanese colonial times, to the beginning of independence in 1945. The hope is that he can refresh about who and how he did. This study used a qualitative approach, namely biogafi research conducted through library research and interviews with informants. Sources of data are taken from documentation, pages on the internet and informants from the Zafry Zamzam family. Zafry Zamzam, a religious national fighter from Kalimantan, is known as a multitalented figure; He has played many roles, starting as a Koran teacher in Surau, a People's School teacher, a journalist, a writer, a politician, a bureaucrat to an academician. In this research, in addition to exploring his views during the struggle which are still relevant to the current problem of national unity facing the Indonesian nation today. His view is that the constitutional form of the Republic of Indonesia which is in line with the spirit of the struggle for independence of the Indonesian nation is Unitarism in the form of a unitary republic of Indonesia, rather than choosing a federalist government system that divides power to the federal state.Keywords: Zafry Zamzam, State Administration, Unitarism and Federalism  AbstrakPenelitian ini ditujukan untuk menggali kembali gagasan besar pejuang nasional asal Kalimantan Zafry Zamzam, selalu gigih memilih Unitarisme sebagai ketatanegaraan Negara Republik Indonesia yang digagasnya sejak masa penjajah Belanda dan Jepang, hingga awal kemerdekaan 1945. Harapannya dapat menyegarkan kembali tentang siapa dan bagaimana sepak terjangnya. Penelitian ini menggunakan pendekatan kualitatif, yaitu penelitian biografi yang dilakukan melalui library reseach dan wawancara kepada informan. Sumber data diambil dari dokumentasi, laman pada internet dan informan dari keluarga Zafry Zamzam. Zafry Zamzam, pejuang nasional agamis asal Kalimantan, dikenal sebagai sosok multitalenta; banyak peran dilakoninya mulai sebagai guru ngaji di surau, guru Sekolah Rakyat, jurnalis, sastrawan, politisi, birokrat hingga akademisi. Dalam penelitian ini disamping untuk menggali kembali tentang pandangannya selama perjuangan yang masih relevan dengan persoalan kesatuan bangsa yang sedang dihadapi bangsa Indonesia saat kini. Pandangannya bahwa bentuk ketatanegaraan Negara Republik Indonesia yang sejalan semangat perjuangan kemerdekaan bangsa Indonesia adalah Unitarisme dalam bentuk negara kesatuan republik Indonesia, daripada memilih sistem pemerintah federalisme yang membagi kekuasaan kepada negara federal.Kata Kunci: Zafry Zamzam, Tata Negara, Unitarisme dan Federalisme